2021
DOI: 10.1002/jsfa.11405
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of differential levels of phosphorus fixation in dolomite and calcium carbonate amended red soil

Abstract: BACKGROUND The pH adjustment of acidic red soils with lime materials is beneficial for the reduction of phosphorus (P) fixation. However, the reasons for varying levels of P activation after adding different lime materials have not been fully investigated. Therefore, this study examined changes in soil labile P and P forms after phosphate application to calcium carbonate (CaCO3) and dolomite amended red soil during a 120‐day incubation period. Also change of P sorption properties in the amended soil samples fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 53 publications
(110 reference statements)
0
5
0
1
Order By: Relevance
“…It has been shown that long-term management practices such as inorganic fertilizer application and manual weeding can lead to negative impacts such as soil acidification, increased bulk weight and decreased soil fertility quality [ 44 ]. Soil acidification accelerates the fixation of free phosphorus elements in the soil [ 42 ], and soil compaction reduces the rate of carbon and nitrogen cycling in the stand [ 45 ], thus exhibiting a significant reduction in fast-acting nutrients in high-generation plantation soils. Studies have shown that soil enzyme activity is significantly associated with stand nutrient cycling and is involved in the mineralization process of organic matter [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that long-term management practices such as inorganic fertilizer application and manual weeding can lead to negative impacts such as soil acidification, increased bulk weight and decreased soil fertility quality [ 44 ]. Soil acidification accelerates the fixation of free phosphorus elements in the soil [ 42 ], and soil compaction reduces the rate of carbon and nitrogen cycling in the stand [ 45 ], thus exhibiting a significant reduction in fast-acting nutrients in high-generation plantation soils. Studies have shown that soil enzyme activity is significantly associated with stand nutrient cycling and is involved in the mineralization process of organic matter [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…NaHCO 3 ‐Pi is adsorbed on the soil surface. NaHCO 3 ‐Pi is a highly active P in soil, which may make it enter water body and run‐off with rain easily, so it may be an important source of CaCl 2 ‐P (Fan et al, 2021; Wang et al, 2021) (Table 5). Uptake by plants and microorganisms results in relatively low concentrations of NaHCO 3 ‐Pi (Cassagne et al, 2000) (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…NaHCO 3 -Pi is adsorbed on the soil surface. NaHCO 3 -Pi is a highly active P in soil, which may make it enter water body and run-off with rain easily, so it may be an important source of CaCl 2 -P (Fan et al, 2021;Wang et al, 2021) (Table 5).…”
Section: The Aggregates P Fractions Distribution and Its Effect On Apmentioning
confidence: 99%
“…Soil acidification accelerates the fixation of free phosphorus elements in the soil [46], and soil compaction reduces the rate of carbon and nitrogen cycling in the stand [6], thus exhibiting a significant reduction in fast-acting nutrients in high-generation plantation soils. Studies have shown that soil enzyme activity is significantly associated with stand nutrient cycling and is involved in the mineralization process of organic matter [47]. Continuous planting significantly affected sucrase, urease, and acid phosphatase activities, and the decrease in the activities of these three enzymes indicated that the cycling of carbon, nitrogen, and phosphorus in the soil was blocked [48].…”
Section: Changes In Soil Fertility and Biological Propertymentioning
confidence: 99%